Post-Disaster Community Empowerment in West Java - Willya Achmad (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze post-disaster community empowerment efforts in West Java Province. The research method used was a qualitative approach with a descriptive design. Data collection was conducted through documentation studies related to the research. The results indicate that natural disasters in West Java over the past ten years have been dominated by floods, landslides, and earthquakes, which have had a significant impact on human safety, infrastructure damage, and disruption to the community's social and economic conditions. The most severe impacts are felt in the post-disaster phase, when communities face loss of livelihoods, limited economic access, housing damage, and psychosocial trauma. Therefore, post-disaster community empowerment is crucial for restoring independence and social resilience through economic recovery, community-based rehabilitation and reconstruction, capacity building and mitigation education, and social and psychosocial support. This allows communities to recover, recover, and become more resilient in the face of potential future disasters.